Given that U is a function of x, y and z and A a vector field, prove that:
∇⋅(UA)=(∇U)⋅A+U(∇⋅A).
"\u2207\u22c5(UA)=\\frac{\\partial}{\\partial x}(UA_x)+\\frac{\\partial}{\\partial y}(UA_y)+\\frac{\\partial}{\\partial z}(UA_z)="
"=\\frac{\\partial U}{\\partial x}(A_x)+\\frac{\\partial U}{\\partial y}(A_y)+\\frac{\\partial U}{\\partial z}(A_z)+\\frac{\\partial A_x}{\\partial x}(U)+\\frac{\\partial A_y}{\\partial y}(U)+\\frac{\\partial A_z}{\\partial z}(U)="
"=(\u2207U)\u22c5A+U(\u2207\u22c5A)"
Comments
Leave a comment